Effects of an extended therapeutic strategy versus standard-of-care therapy on persistent acute kidney injury in high-risk patients after major surgery: study protocol for the randomised controlled single-centre PrevProgAKI trial - Joachim Gerss; Melanie Meersch; Carola Wempe; Alexander Zarbock; John Kellum; Christian Strauss; Thilo von Groote; Mahan Sadjadi; Hendrik Booke; Ludwig Maximilian Schöne; Leonie Sauermann (BMJ Open)
Introduction Persistent acute kidney injury (AKI) is associated with an increased morbidity and mortality. In patients with an already established AKI, the new urinary biomarker C-C motif chemokine ligand 14 (CCL14) can predict a persistent AKI. However, it is still unknown whether the implementation of nephroprotective measures in patients with an already established moderate/severe AKI can positively influence the trajectory of AKI and patients’ outcome.Methods and analysis The PrevProgAKI trial is a randomised, controlled, single-centre trial designed to evaluate the effectiveness of nephroprotective measures in patients with established moderate/severe AKI. We aim to enrol 480 patients with moderate or severe AKI (Kidney Disease: Imroving Global Outcomes, KDIGO, stage 2 or 3) within 72 hours of major surgery. Eligible patients will be randomised to receive either standard of care (control group) or an extended therapeutic strategy that consists of different supportive measures (intervention group). The randomisation will be stratified by urinary CCL14 results (CCL14<1.3 ng/mL or CCL14≥1.3 ng/mL). Treating physicians will be blinded to the test results. The primary endpoint is a composite of the development of persistent severe (stage 3) AKI, need for renal replacement therapy or death within 72 hours. The key secondary endpoint is the composite of death, initiation of renal replacement therapy within 90 or persistent renal dysfunction at day 90.Ethics and dissemination The PrevProgAKI trial has been approved by the Ethics Committee of the Chamber of Physicians Westfalen-Lippe and the University of Muenster (no. 2021-569 f-S). Results will be disseminated widely and published in peer-reviewed journals, presented at conferences and will guide patient care and further research.Trial registration number NCT05275218 (clinicaltrials.gov), first posted 11 March 2022.